Planning Through Hydrological Maps - Palaniappan, A.B. (Journal of Soil and Water Conservation, 2022)
Systematic data collection in Water resources sector created large volume of data. Although they are scare, they are very useful for planning purposes. At present due to poor presentation, the valuable information are not available to planners. Hydrological maps are recommended for this purpose. These maps provide hydrologithal information and its spatial relationship. Maps have advantage that they speak beyond the language barrier. Efforts are to be made to prepare guidelines for the preparation of hydrological maps.